Isolamento e diferenciação das células-tronco da polpa dentária canina em células progenitoras neurais - Rosa, Matheus Pippi da (2018)
The development of research that promotes the understanding of the mechanisms of neurogenesis is important for the treatment of many degenerative neurological diseases in humans and animals. However, obtaining neural stem cells for isolation and in vitro culture requires the collection of tissues vital to the patient. The restriction of access of these tissues and limitations in experimental practice has encouraged researchers to seek alternatives using the differentiation potential presented in stem cells of the adult individual. The aim of the study was to verify the differentiation capacity of canine dental pulp stem cells in neural progenitor cells when stimulated in vitro, and quantify the attainment and viability of the undifferentiated cells, during three cell culture passages. Dental pulp cells were isolated from two dogs, with ten months age around, that died due to automobile trauma. Cells were expanded for three days in cell culture and cell number and cell viability evaluations were performed. Subsequently, neural differentiation was performed in induction medium culture. The post-induction immunophenotypic profile was evaluated using flow cytometry and fluorescent immunocytochemistry tests. Spherical cell groupings, consistent with neurospheres, were observed seven days after. It was possible to verify high expression of anti-nestin and anti-GFAP neural markers after 14 days, suggesting that the undifferentiated dental pulp canine stem cells are able to present neural differentiation, through appropriate stimuli. Dental pulp canine has been shown to be highly capable of delivering viable undifferentiated stem cells.